A robotic concepts: Study of perceived brand reputation and customers' perceived performance in a restaurant - Rasidah Hamid; Fazrul Reza Mohd Fadzil; Mohd Hanafi Azman Ong; Abdul Aziz Azdel (Global Business & Finance Review (GBFR), 2023)
Purpose: Budget, hygiene factors, and the issue of workforce shortages have accelerated the use of robotics technology in restaurant chains. Even though service robots could operate many functions and roles, further research is required in hotel settings to ascertain how various combinations of robots and humans at different product/service tiers may affect customers' viewpoints and intentions. Design/methodology/approach: This research study addressed the issue of data collected from 364 customers in Malaysia. This study examines both theoretical and managerial insights. Findings: The findings of the study on product theory and performance, the use of robots in core and facilitating product levels is far less likely to enhance consumers' perceived performance and brand reputation. The perceived performance of consumers' services influences their brand reputation and repurchase intention. Consumers' repurchase intention is only positively affected by their perceived brand reputation. Research limitations/implications: This study employs an experimental design approach to investigate the use of robots in the restaurant context. Future research could focus on customers' real-world dining experiences with robot technology. Future research could be used to confirm the findings of this paper. All samples were collected from the Malaysia population, where diners' behavioral intentions toward robots may differ due to cultural differences. Thus, future studies in developed and developing countries are suggested to validate the research findings. Originality/value: The study adds to the literature on the product-level theory, robots versus human employees, brand and service performance, and behavioral intentions in the restaurant setting. The findings have ramifications for how robotic restaurants can improve restaurant image, expedite performance output, and mitigate the impact of the pandemic.
Keywords: 650; Robot; brand reputation; customers' perceived performance; restaurant